Distribution System Optimization at one of the Food Distributors in Gowa Regency - Dwi Handayani; Muhammad Rusman; Kasmiati; Maula Sidi Muhammad; Raodah (Engineering Faculty, UNSOED, 2025)
PT XYZ is a manufacturing company that produces soy sauce, chili sauce, tomato sauce, vinegar and syrup which also acts as a distributor of its products.. Product distribution is carried out through traditional channels by salesmen. However, the determination of salesman visit routes is still based on experience so that it is not optimal in terms of distance, time, and cost. This study aims to develop an algorithm to produce a more efficient salesman visit route at PT XYZ. Data were collected through interviews with the owner and salesmen, then analyzed using tabu search and genetic algorithms with MATLAB software. The results show that both algorithms are able to produce a more optimal route than the existing route. The initial route has a distance of 63.74 km, a travel time of 177 minutes, and a cost of Rp 54,181. The tabu search and genetic algorithms produce a route with a distance of 62.68 km, a travel time of 174 minutes, and a cost of Rp 53,278. Both algorithms provide savings of around 2% compared to the initial route. The superiority of the tabu search algorithm can be seen from the much faster computing time (0.005381 seconds) compared to the genetic algorithm (113.02 seconds), while still finding the optimal solution. This study recommends the use of the tabu search algorithm to optimize salesman visit routes for distribution efficiency at PT XYZ.